2011
DOI: 10.1128/aem.05962-11
|View full text |Cite
|
Sign up to set email alerts
|

Semicontinuous Culture of Magnetospirillum gryphiswaldense MSR-1 Cells in an Autofermentor by Nutrient-Balanced and Isosmotic Feeding Strategies

Abstract: An improved strategy was developed for the high-density culture of Magnetospirillum gryphiswaldense strain MSR-1 and large-scale magnetosome production in both 7.5-and 42-liter autofermentors. By using a nutrientbalanced feeding strategy and the replacement of carbon and nitrogen sources to reduce accumulation of Na ؉ and Cl ؊ ions, we reduced the factors that tend to inhibit cell growth, particularly the increase of osmotic potential. Semicontinuous culture was thereby achieved in the autofermentor for the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
125
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(132 citation statements)
references
References 20 publications
5
125
1
Order By: Relevance
“…Despite some progress by growth optimization (22,34), previous attempts to increase magnetosome yields at a large scale were met by only limited success. In this work, we established a strategy to enhance magnetosome production by genetic engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some progress by growth optimization (22,34), previous attempts to increase magnetosome yields at a large scale were met by only limited success. In this work, we established a strategy to enhance magnetosome production by genetic engineering.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Zhang et al [47] reported high-density cultivation of M. gryphiswaldense in a large-scale fermentor. Furthermore, the overexpression of magnetosome biosynthesis genes by genomic multiplication in M. gryphiswaldense led to nearly threefold increased overproduction of magnetosomes.…”
Section: Strainmentioning
confidence: 99%
“…Therefore, it seems likely that any of these growth factors, if necessary, are synthesized by M. blakemorei. Vitamin addition was also deemed unnecessary for the growth of M. gryphiswaldense, and thus, vitamins were eliminated from the growth medium in studies involving other magnetotactic bacteria (12). Our data indicated that high iron concentrations might have a potentially deleterious effect on M. blakemorei cell growth, but we retained it in the growth medium at a constant concentration (through injection of pulses of iron) since it is absolutely required for magnetosome biomineralization.…”
mentioning
confidence: 75%